2019
DOI: 10.1021/acsami.9b04682
|View full text |Cite
|
Sign up to set email alerts
|

NiOx Nanoflower Modified Cotton Fabric for UV Filter and Gas Sensing Applications

Abstract: Integration of multifunctional nanomaterials with textiles could be a significant value addition to the bright future of the growing technology "Technical Textiles". Development of textiles with antielectromagnetic radiation and in particular antiultraviolet features could be one of the best solutions to the ozone depletion induced ultraviolet pollution of the environment, which is a major concern in the context of surging skin cancer cases. In this background, multifunctional nanoflower structured partial hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 66 publications
0
19
0
Order By: Relevance
“…The FTIR spectra of PET, viscose and 50:50 PET:viscose emeraldine salt-coated fabrics indicated the presence of polyaniline on the fabric surfaces ( Figure 3). The peak at 1308-1340 cm⁻ 1 Hence, it was observed that the concentration of PANI and the type of fabric influence the amount of polyaniline that is incorporated into the fabric. While the PANI concentration has a greater effect at lower concentrations levels, the fabric chemical nature is dominant at higher ones.…”
Section: Ftir Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The FTIR spectra of PET, viscose and 50:50 PET:viscose emeraldine salt-coated fabrics indicated the presence of polyaniline on the fabric surfaces ( Figure 3). The peak at 1308-1340 cm⁻ 1 Hence, it was observed that the concentration of PANI and the type of fabric influence the amount of polyaniline that is incorporated into the fabric. While the PANI concentration has a greater effect at lower concentrations levels, the fabric chemical nature is dominant at higher ones.…”
Section: Ftir Analysismentioning
confidence: 99%
“…During the past decade, functional textiles have received industrial consideration as well as research attention. In particular, fabrics coated with tailored functional materials have been introduced in the cosmetic, pharma, electronic and medicinal fields for therapeutic, controlled release, protecting, sensing, and monitoring applications [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Among the different types of functional textiles, antibacterial ones are receiving increasing research and development interest due to health risks associated with infectious bacteria and epidemic outbreaks of viruses throughout the world.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that UV light gets absorbed by the UV filter when it is exposed to UV radiation resulting in null transmittance. [ 25 ] The null transmittance property was attained because both the β‐Bi 2 O 3 and SnO 2 molecules have very high UV absorption, which allows them to absorb UV radiation and backscatter non‐transmitted UV radiation, making the polypropylene cloth coated β‐Bi 2 O 3 /SnO 2 a promising UV protection material. [ 26 ] UV filter application could also be extended for wide bandgap semiconductors based on the absorption coefficient, biocompatibility, and availability of the similar structured metal oxides (Ga 2 O 3 ,ZnO).…”
Section: Resultsmentioning
confidence: 99%
“…Note that CeO 2 [109] and flower-like NiO x structures have been also considered. [110] The nanoparticles can be synthesized in situ within the material matrix or ex situ and then added to the matrix. The ex situ approach offers tighter control over NP synthesis, polydispersity, stabilization, and loading into the matrix, all of which enable efficient UV blocking optimization.…”
Section: Biobased Materials Doped With Uv-absorbersmentioning
confidence: 99%